Comment on 'Wetzeliella and its allies – the 'hole' story: a taxonomic revision of the Paleogene dinoflagellate subfamily Wetzelielloideae' by Williams et al. (2015). (3rd July 2017) - Bijl, Peter K.; Brinkhuis, Henk; Egger, Lisa M.; Eldrett, James S.; Frieling, Joost; Grothe, Arjen; Houben, Alexander J. P.; Pross, Jörg; Śliwińska, Kasia K.; Sluijs, Appy
ABSTRACT: The taxonomic revision of the dinoflagellate cyst subfamily Wetzelielloideae by Williams et al. (2015) places primary emphasis on the type of archaeopyle, and secondarily on wall ornamentation. Williams et al. (2015) argues that this provides more clarity for taxonomic differentiation within the subfamily of Wetzelielloideae, and adds to the stratigraphical significance of species within. We find, however, that their proposed revision (1) introduces taxonomic criteria that divert drastically from these in other dinoflagellate cyst subfamilies, (2) unnecessarily erects and emends many new genera and species, and (3) poses serious practical limitations, which together (4) lead to profound reduction of the stratigraphical applicability of many marker species. In this contribution, we substantiate our concerns regarding the approach and criteria used by Williams et al. (2015). We propose to retain the generic definitions of Wetzelielloideae that existed prior to the revisions by Williams et al. (2015), until a revision supported by the community is available.